Oral squamous cell carcinoma vs. medication-related osteonecrosis of the jaw in patients assuming bone-modifying agents: a diagnostic challenge in a multi-hospital case series - Mauceri, Rodolfo; Coppini, Martina; La Mantia, Gaetano; Seminara, Giuseppe; Pérez-Sayáns, Mario; Toro, Corrado; Vitagliano, Rita; Kawamata, Hitoshi; Hyodo, Toshiki; Colella, Giuseppe; Rodolico, Vito; Campisi, Giuseppina (Frontiers in Oral Health, 2025)
BackgroundDespite advances in the diagnosis of oral squamous cell carcinoma (OSCC), most cases are diagnosed in advanced stages, influencing negatively the patient's prognosis. The absence of specific signs and symptoms contributes to the diagnostic delay of OSCC, often leading to confusion with various oral conditions, including, in patients with a history of bone modifying agents (BMA) and/or anti-angiogenic (AA) molecules, the Medication-Related Osteonecrosis of the Jaw (MRONJ). This study aims to investigate the characteristics of OSCC and MRONJ, focusing on clinical and radiological features of a multicenter series.MethodsAccording to STROBE statements, 11 patients collected by different centers and affected by OSCC undergoing BMA or AA therapy, with clinical and radiological features resembling MRONJ were reported (6 in Italy and 5 in Japan). Due to the suspicion of a malignant neoplasia, incisional biopsies for histological examination were performed.ResultsIn all eleven patients under ONJ-associated therapy, discerning between OSCC and MRONJ was a real challenge due to overlapping clinical and radiological features. The present case series highlights the importance of considering the possibility of malignant disease in patients undergoing ONJ-associated therapy.ConclusionAlthough biopsy is commonly considered unnecessary for MRONJ diagnosis, our findings highlight the importance of selectively performing bioptic procedures in patients taking ONJ-associated therapy to exclude the malignant nature of oral lesions promptly.